Successful treatment of cystic lesion combining Cystectomy, Nonsurgical Endodontics and Vital Pulp Therapy of Mature Permanent Mandibular Molars: a Case Report with 19 Months Follow-Up - Roberta Zamaliauskiene; Rita Veberiene (eJournal of Oral Maxillofacial Research, 2023)
Background: Clinical examination revealed large periapical lesion. Patient was referred for endodontic treatment of right mandibular first and second molars before planed cystectomy. The aim of this case report is to present the clinical approach to preserve healthy pulp tissue by combining nonsurgical root canal treatment and vital pulp therapy for mature mandibular molar.